Inquiry examining the influence of school and family on high-level athletic participation - Casolo, F.; Frattini, G.; Mondoni, M.; Cilento, F.; Taiana, M.; Tessera, S.; Vago, P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The question explored in this research was to know what drives a youngster to pick a particular sport and the factors that influenced this decision. This study focused on two variables 1) the choice of a particular sport; 2) the continued participation in competitive sports career. In data gathering we used questionnaires, the subjects were asked to rate the questions using a scale similar to the Likert scale (from 0 being of little importance to 6 being of very important). The research sample consists of 116 Italian athletes 88 males and 28 females, 53 of these athletes are below or 20 years old, 63 of them are older. 15 of them practice individual sports, while 101 practice team sports. Factor analysis of the data have been done on the questionnaires administered and the matrixes of correlation have been analyzed with Principal Components (Oblimin Rotation) using SPSS v 10.0 (Statistical Package for Social Sciences). Factor analysis have simplified the variables, in order to have a limited numbers of factors, the most significant ones were interpreted. School Factors (FSc): F1Sc=School as a support for sport activities; F2Sc=School as an obstacle. Family Factors (FF):F1F=Family balance as promoter of sports activities; F2F=The parents and the sport; F3F=Influence of the family`s economic condition; F4F=The sport activity and family responsibilities. For each factor have been calculated the Cronbach`s alpha in order to test internal reliability. The results regarding school and family factors are the following: F1 Sc(945; = 0.87) F2Sc(945; =0.65) F1F (945; =0.69) F2 F(945; =0.57) F3 F (945; =0.56) F4 F (945; =0.40). The data proved that school does not significantly influence the choice of the sport: F2Sc it prevails little over F1Sc. It was found the female samples over 20, who practiced an individual sport perceived school as obstacle when asserting themselves as athletes. All the subjects interviewed stated that the greatest factor in their continuation of a competitive sports career was determined by their sound family life with a mean of Factor 1 (F1F), for every sample group there was a number that was over the value of 4; females older than 20 years old, practicing an individual sport proved a factor of 4 (F4F). This prevailed in deciding to continue in the pursuit of a competitive sports carrier. Conclusions: The school does not influence the choice of the continuation of a competitive sports career, it does however, sometimes prove to be an obstacle. A sound family life is proven fundamental for the practice of the competitive sport and it is a great support when trying to execute the desire to continue.